Bibliometric Analysis of Dendritic Epidermal T Cell (DETC) Research From 1983 to 2019 - Deng, Ziqin; Wang, Hongwei; Chen, Zhiye; Wang, Ting (Frontiers in Immunology, 2020)
Dendritic epidermal T cell (DETC) is a group of immune cells expressing canonical γδ TCR in murine epidermis. Similar to γδ T cells in human epidermis, it is an important barrier cell of skin and participates in skin immune surveillance, immune regulation, skin homeostasis, tissue protection and other activities. Since its discovery in 1983, research on DETC has grown rapidly and unevenly. To evaluate the DETC research trends and map the knowledge structure of DETC research, bibliometric methods and techniques are applied. A total of 384 DETC related articles derived from Scopus database published from 1983 to 2019 are analyzed with indicators of publication and citation metrics, country and international cooperation, author and co-authorship, and keyword co-occurrence cluster. The present research status, the emerging global trends and the future development direction are also visualized, prospected and discussed. In summary, this study provides a novel and useful data for DETC research scientific community, and helps them explore DETC more intuitively and effectively.